2015
DOI: 10.1186/s13041-015-0094-1
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl-D-aspartate receptors mediate activity-dependent down-regulation of potassium channel genes during the expression of homeostatic intrinsic plasticity

Abstract: BackgroundHomeostatic intrinsic plasticity encompasses the mechanisms by which neurons stabilize their excitability in response to prolonged and destabilizing changes in global activity. However, the milieu of molecular players responsible for these regulatory mechanisms is largely unknown.ResultsUsing whole-cell patch clamp recording and unbiased gene expression profiling in rat dissociated hippocampal neurons cultured at high density, we demonstrate here that chronic activity blockade induced by the sodium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 92 publications
2
55
1
Order By: Relevance
“…2), whereas previously we found that synaptic upscaling caused by DNMT inhibition was not dependent on NMDA receptor signaling (34). These observations are consistent with other studies showing that homeostatic intrinsic plasticity relies on NMDA receptor signaling, whereas homeostatic synaptic upscaling does not (54, 55, 101, 102). However, an additional layer of complexity is that the molecular mechanisms that regulate homeostatic synaptic downscaling are not inverse of those that regulate homeostatic synaptic upscaling; in particular, downscaling depends on NMDA receptor signaling (103).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…2), whereas previously we found that synaptic upscaling caused by DNMT inhibition was not dependent on NMDA receptor signaling (34). These observations are consistent with other studies showing that homeostatic intrinsic plasticity relies on NMDA receptor signaling, whereas homeostatic synaptic upscaling does not (54, 55, 101, 102). However, an additional layer of complexity is that the molecular mechanisms that regulate homeostatic synaptic downscaling are not inverse of those that regulate homeostatic synaptic upscaling; in particular, downscaling depends on NMDA receptor signaling (103).…”
Section: Discussionsupporting
confidence: 93%
“…4C). Additionally, homeostatic intrinsic plasticity caused by prolonged exposure to TTX is associated with decreased expression of genes encoding voltage-gated K + channels, Ca 2+ -activated K + channels, and tandempore K + channels (55). Collectively, these observations suggest that dynamic alterations in DNA cytosine methylation broadly affect the expression of genes encoding ion channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When neural activity is suppressed, many of the activity-induced genes show a slightly dampened expression compared to the basal culture condition, which could also be related to the neuron’s compensatory response to maintain a stable firing rate. For example, chronic activity blockade of hippocampal neurons resulted in an overall reduction of potassium current with a concomitant decrease in expression levels of voltage-gated K V 1 and K V 7 potassium channels, which was explained as a mechanism for the homeostatic increase in intrinsic excitability (Lee et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Some of these K + channel genes (e.g., KCND2 , KCNK3 , KCNMA1 , KCNQ2/3 ) were also differentially expressed in postmortem human frontal cortex, amygdala, or NAc from alcohol dependent individuals (Flatscher-Bader, Harrison, Matsumoto, & Wilce, 2010; Liu et al, 2006; Ponomarev et al, 2012). Recent studies show that activity-dependent processes regulate K + channel gene expression, including Kcnmb2 , Kcnn1 , Kcnq3 , and Kcnv1 (Lee et al, 2015), and NMDA receptor activity can modulate surface trafficking and function of K Ca 2, K V 2.1, and K V 4.2 K + channels (Kim, Jung, Clemens, Petralia, & Hoffman, 2007; Mulholland et al, 2008; Ngo-Anh et al, 2005). Because chronic ethanol exposure results in imbalances in NMDA receptor expression and synaptic transmission, we speculate that CIE-induced adaptations in some K + channel genes are compensatory mechanisms to counterbalance chronic ethanol inhibition of NMDA receptor activity, whereas adaptations in other K + channel genes may be protective against or facilitate escalation of drinking in dependent BXD mice.…”
Section: Discussionmentioning
confidence: 99%